Understanding Freedom and Human Rights in Africa - Obioha, Precious Uwaezuoke (Covenant University Journal of Politics and International Affairs, 2017)
The issues of human rights and freedom are topical in most socio-political discourse especially in the African continent given the plethora of cases of human rights abuse and unnecessary curtailment and most times outright denial of freedom to citizens. This constitutes a serious bane to the flowering of human potentialities and the general human well -being. This anomaly has however continued unabated despite the volumes that have been written on the subjects and seminars and conferences held on the same. This paper, through the analytic and critical methods, argues that much may not be achieved until the philosophical foundation upon which these subjects rest is well articulated and appreciated. The paper equally claims that one of the ways of enhancing the respect for human rights and freedom in Africa is to recognize the symbiotic relationship between the two subjects. The paper finally argues that an integral view of human freedom/rights which recognizes not only freedom-from but also freedom-to and rights-to, is foundational for the promotion of human well-being.